2021
DOI: 10.1021/acssuschemeng.1c05120
|View full text |Cite
|
Sign up to set email alerts
|

Greening Pathways for Synthetic Talc Production Based on the Supercritical Hydrothermal Flow Process

Abstract: Recent efforts in chemistry have led to development of a fast and continuous process for the production of synthetic talc in a supercritical hydrothermal reactor. This attractive process compatible with industrial requirements leads to advantageous physicochemical characteristics including submicrometer size, hydrophilicity, and high chemical and mineralogical purity. In addition, the high speed of the process and moderate reaction conditions have potential advantages from a viewpoint of the impacts on the env… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 35 publications
0
6
0
Order By: Relevance
“…Recently, the cradle-to-gate environmental LCA analysis related to the SHFS of talc was evaluated by Glogic et al 154 At the maximal reagents' concentration yielding 76 g L À1 of talc, the precursors account for 94% of the impacts. In particular, sodium metasilicate, employed as the silicon source, contributes solely to 40-60% of the total impacts, depending on the synthesis reaction.…”
Section: Life Cycle Assessment Of Supercritical Fluid-based Synthesismentioning
confidence: 99%
“…Recently, the cradle-to-gate environmental LCA analysis related to the SHFS of talc was evaluated by Glogic et al 154 At the maximal reagents' concentration yielding 76 g L À1 of talc, the precursors account for 94% of the impacts. In particular, sodium metasilicate, employed as the silicon source, contributes solely to 40-60% of the total impacts, depending on the synthesis reaction.…”
Section: Life Cycle Assessment Of Supercritical Fluid-based Synthesismentioning
confidence: 99%
“…24 Several studies have demonstrated that there is an avenue to evaluate their environmental performance through the life cycle assessment (LCA) methodology. 25,26 The LCA methodology has been widely used to assess the environmental sustainability of new products and emerging technologies in the early stages. 27 In particular, this methodology has been used in different fields that involve nanomaterials such as photovoltaic systems, 28 soil remediation, 29 water remediation, 30 lithium-ion batteries using silicon nanotubes for electric vehicles, 31 and biogas production.…”
Section: ■ Introductionmentioning
confidence: 99%
“…However, the scaling-up of emerging technologies from the laboratory to the industrial scale involves various challenges, including adaptability to other materials, complex manufacturing and operating processes, and determining their environmental impact . Several studies have demonstrated that there is an avenue to evaluate their environmental performance through the life cycle assessment (LCA) methodology. , …”
Section: Introductionmentioning
confidence: 99%
“…Although these inorganic fillers are in general not costly, they may cause some environmental and health concerns. For instance, for talc, raw material extraction often involves mining activities that destroy or pollute natural habitats [9]. Furthermore, naturally occurring talc is often contaminated with asbestos, a known carcinogen, raising some concerns about the occupational health of the workers who handle these fillers [10].…”
Section: Introductionmentioning
confidence: 99%
“…Recently synthetic inorganic nanoparticles, such as molecular-sieve [12] and talc nanoflakes [13,14], and lightweight synthetic polymers, such as fluoroelastomers [15] and polydimethylsiloxane (PDMS) [16], have also been demonstrated as efficient nucleating agents for scCO 2 foaming of PP. Nevertheless, the syntheses of these nanomaterials all involve relatively expensive chemical processes or non-eco-friendly chemicals [9,17].…”
Section: Introductionmentioning
confidence: 99%